2008
DOI: 10.1038/sj.bjc.6604394
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-S-transferase M1, T1 and P1 polymorphisms, and breast cancer risk, in BRCA1/2 mutation carriers

Abstract: 5The Royal Marsden NHS Foundation Trust, Sutton, UK Variation in penetrance estimates for BRCA1/2 carriers suggests that other environmental and genetic factors may modify cancer risk in carriers. The GSTM1, T1 and P1 isoenzymes are involved in metabolism of environmental carcinogens. The GSTM1 and GSTT1 gene is absent in a substantial proportion of the population. In GSTP1, a single-nucleotide polymorphism that translates to Ile112Val was associated with lower activity. We studied the effect of these polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…Notably, the GSTP1 105Val variant, which was previously reported to be associated with increased risk of breast cancer in a small study of 90 BRCA2 carriers [20], was associated with non-significant reduced risk for BRCA2 carriers in our larger sample of 245 women with BRCA2 mutations. Although the sample size of this study is still relatively small, there is a statistically significant difference ( P = 0.02) between the HR for BRCA2 in this study and that reported by Kadouri et al [20]. These results support the need for replication studies to confirm or refute hypothesis-generating studies, including analyses that use existing unpublished data collated by consortia.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Notably, the GSTP1 105Val variant, which was previously reported to be associated with increased risk of breast cancer in a small study of 90 BRCA2 carriers [20], was associated with non-significant reduced risk for BRCA2 carriers in our larger sample of 245 women with BRCA2 mutations. Although the sample size of this study is still relatively small, there is a statistically significant difference ( P = 0.02) between the HR for BRCA2 in this study and that reported by Kadouri et al [20]. These results support the need for replication studies to confirm or refute hypothesis-generating studies, including analyses that use existing unpublished data collated by consortia.…”
Section: Resultsmentioning
confidence: 51%
“…However, their effects on breast cancer risk in carriers of BRCA1 or BRCA2 mutations have been reported in only a single study [20]. Their analysis of 320 BRCA1/2 carriers showed no evidence for altered risk of breast cancer for individuals with the GSTT1 and GSTM1 deletion variants, but did report that the GSTP1 Ile105Val variant was associated with increased breast cancer risk (HR 1.36 ( p = 0.04) for heterozygotes, and HR 2.00 ( P = 0.01) for homozygotes).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CFHR3 and CFHR1 are associated with age-related macular degeneration [43-45] and systemic lupus erythematous [46]. GSTT1 has been linked to breast cancer [47], NAFLD to non-alcoholic fatty liver disease [48], and HLA-DRB5 and HLA-DQA1 to autoimmune diseases [49,50]. Due to their functional characteristics, most of these genes are very appealing from both biomedical and evolutionary perspectives, supporting the idea that the variable prevalence of some diseases among ethnic groups is in part linked to environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that the GSTP1 polymorphism is associated with a higher risk of breast cancer especially Ile/Val and Val/Val allele carriers in different population such as Americans (Kadouri et al, 2008), Indians (Samson et al, 2007;Saxena et al, 2009), Chinese in North china (Ge et al, 2013) and Chinese in Southeast China (Lee et al, 2008). On the other hand, studies of the Finnish (Mitrunen et al, 2001) and Koreans (Kim et al, 2004) revealed that the variant allele of GSTP1 was connected with a reduced breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%